Bad blood - Fairstein, Linda A. (Fairstein, Linda A. Alexandra Cooper novels., 2007)
In the middle of an unusual trial involving a young businessman charged with murdering his wife, Manhattan prosecutor Alexandra Cooper sees the city thrown into chaos when an explosion of unknown origin erupts 600 feet below street level, an event she is summoned to investigate when it is traced back to her case.